Rechtstitel und Herrschaftssymbol Studien zum Umgang der Empfänger in Italien mit Verfügungen Friedrichs II. (1194-1250) - Vogeler, Georg (Bibliothek des Deutschen Historischen Instituts in Rom, 2019)
This study investigates for the first time in detail the specific context for the use of documents prepared for recipients in Italy by the Staufer Frederick II (1198-1250). It compares the texts used for typical writings in communal Italy with the bureaucratic Regnum Siciliae, thereby addressing the issue of the function of written documents with a focus on the symbolic communication of authority.